Surgical Sabermetrics: Applying Athletics Data Science to Enhance Operative Performance. Issue 2 (29th June 2021) - Yule, Steven; Janda, Allison; Likosky, Donald S.
Abstract : Mini-abstract: Surgical sabermetrics is advanced analytics of digitally recorded surgical training and operative procedures to enhance insight, support professional development, and optimize clinical and safety outcomes. This perspectives article illustrates how surgery can leverage data science approaches in athletics and industry to transform individual and team performance in the operating room.